Ion channels and atrial fibrillation: mitophagy as a key mediator - Wu, Xize; Yan, Xiaorui; Ma, Ruoxi; Wu, Qiuying; Pan, Xue; Wu, Qihua; Ren, Jiaqi; Huang, Yuxi; Gao, Shan; Li, Yue; Gong, Lihong (Frontiers in Physiology, 2025)
BackgroundThe prevalence of atrial fibrillation (AF) is increasing due to the aging population. Mitophagy is crucial for maintaining cardiomyocyte function, while ion channels play a key role in cardiac electrical activity. Dysfunction of ion channels can trigger AF. However, the role of mitophagy-related ion channel genes in AF remains unclear.MethodsAF-related datasets GSE41177 and GSE79768 were merged and batch-corrected for differential expression analysis. Mitophagy-related and ion channel-related genes were obtained from the MsigDB and GeneCards databases. Immune infiltration and functional enrichment analyses were performed. Sixty-five machine learning models were developed to identify Hub genes, with the optimal model selected based on receiver operating characteristic curves, F1 scores, and accuracy. An acute electrical remodeling model of atrial tachyarrhythmia was established in Sprague-Dawley rats by administering a mixture of acetylcholine-calcium chloride for 7 days. Hematoxylin-eosin, Masson, and Sirius red staining were used to detect histopathologic changes in the atrial myocardium. The expression of AF-related mitophagy ion channel genes and proteins was measured by qRT-PCR and Western blotting.ResultsA total of 444 differentially expressed genes in AF were identified, and 9 AF-related mitophagy ion channel genes (AFRMICGs) were obtained (BAX, CTNNB1, DPYSL2, EPHX1, GLUL, GNB2, MIF, MYC, TLR4). Functional enrichment analysis indicated that the pathogenesis of AF is related to inflammation, immune response, ion channels, apoptosis, and various organelles and is associated with the PI3K/AKT, NF-kappa B, JAK-STAT, and mTOR pathways. Immune infiltration analysis showed higher resting dendritic cells and neutrophils and lower follicular helper T cells, M2 macrophages, and activated dendritic cells in AF patients. The glmBoost + Lasso model identified 4 Hub genes: BAX, GLUL, MIF, and TLR4. In vivo experiments showed disordered myocardial cell arrangement, collagen fiber proliferation, interstitial widening, fibrous septa formation, and uneven cytoplasmic staining. qRT-PCR results showed upregulation of BAX, MIF, TLR4, SLC8A1, and CaMKII genes, while the expression of Nav1.5, Kv1.5, hERG, Cav1.2, Cav1.3, Cav3.2, PINK1, Parkin, FUNDC1, BNIP3, NIX, MAP1LC3A, and MAP1LC3B genes was downregulated. Western blotting confirmed increased protein expression of BAX, MIF, and TLR4, whereas GLUL expression showed no significant difference at either the gene or protein level.ConclusionBAX, MIF, and TLR4 are key genes linking mitophagy and ion channels in AF, which appear to influence the immune microenvironment by modulating immune cell infiltration.